Reducing pesticides and increasing crop diversification offer ecological and economic benefits for farmers—A case study in Cambodian rice fields - Sattler, Cornelia; Schrader, Julian; Flor, Rica Joy; Keo, Makarakpakphea; Chhun, Sokunroth; Choun, Saban; Hadi, Buyung Asmara Ratna; Settele, Josef (MDPI, 2021)
Rice production is often associated with high pesticide input. To improve farmers’ practice, sustainable management approaches are urgently needed, such as ecological engineering (EE), which aims at enhancing beneficial arthropods while reducing pesticides. Here, we implemented and tested EE in Cambodian rice fields by comparing: (i) fields not treated with pesticides (control); (ii) fields not treated with pesticides but with non-rice crops planted in the surrounding (EE); and (iii) conventionally farmed fields using pesticides (CR). Using benefit-cost analysis, we compared the economic value of each treatment. The non-rice crops preferred by men and women farmers as well as farmers’ willingness to implement EE were assessed using surveys. We sampled arthropod abundance and richness in rice fields and bunds during two seasons. During the dry season, we compared EE and CR among three Cambodian provinces. During the wet season, we specifically assessed the differences in EE, control and CR in arthropod abundance and rice yield in one province. While withholding from using pesticides did not result in a decrease in yield in EE and control treatments, parasitoid abundance was higher in both treatments during the wet season. The benefit–cost ratio was highest for EE and control treatments. Pesticides were likely the main driver causing low arthropod abundance, without any benefit towards increased rice yield. The proper implementation of EE coupled with farmers’ knowledge of ecologically based pest management is a promising solution towards sustainable rice production.